Evolution of phase segregation and eutectic structures in AgPb18SbTe20. Issue 6 (21st May 2014) - Dadda, Jayaram; Müller, Eckhard; Perlt, Susanne; Höche, Thomas; Hermann, Raphael; Neubrand, Achim
<x xml:space="preserve">Abstract</x> The evolution of phase segregation in stoichiometric quenched AgPbmSbTe2+m (m = 18, Lead–Antimony–Silver–Tellurium – LAST‐18) compounds was studied starting from the known pseudo‐binary diagrams among Ag2Te, PbTe, Sb2Te3 and AgSbTe2. The compositions of secondary phases indicate that liquid phase during cooling, even under quenching conditions, follows mainly the liquidus line on the 2PbTe–Ag0.45Sb0.55Te1.05 quasi‐binary section of the phase diagram until it reaches a critical point (18 mol.% of 2PbTe) and then turns to Ag2Te‐ and Sb2Te3‐rich sides of quasi‐ternary system. This has led to the formation of various secondary phases at various stages during the solidification, whose microstructural features and morphology strongly depend upon their chemical composition. Moreover, during solidification the local compositional fluctuations of liquid phase in combination with the shift of liquid composition towards Sb‐rich side of the phase diagram resulted in the development of eutectic microstructures in some regions of LAST‐18 matrix phase. This suggests there exists a miscibility gap and eutectic point below 600 °C on the 2PbTe–Ag0.45Sb0.55Te1.05 boundary line. These eutectic lamellar structures with a cumulative composition close to LAST‐3 are on the 200–500 nm length scales and possess thermal conductivity of 0.55–0.65 W/m K at room temperature. The low thermal conductivity of lamellar eutectic structures was later confirmed on bulk samples using laser flash analysis, where the samples were synthesized by quenching and annealing. The results clearly demonstrate that one can engineer the microstructures in LAST compounds by selecting the appropriate initial composition from quasi PbTe–Ag2Te–Sb2Te3 ternary phase diagram to lower the thermal conductivity further.